2010
DOI: 10.4061/2010/573138
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Tau-Mediated Synaptic and Neuronal Degeneration in Alzheimer's Disease

Abstract: Patients suffering from Alzheimer's disease (AD) are typified and diagnosed postmortem by the combined accumulations of extracellular amyloid plaques and of intracellular tauopathy, consisting of neuropil treads and neurofibrillary tangles in the somata. Both hallmarks are inseparable and remain diagnostic as described by Alois Alzheimer more than a century ago. Nevertheless, these pathological features are largely abandoned as being the actual pathogenic or neurotoxic factors. The previous, almost exclusive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 61 publications
2
38
0
1
Order By: Relevance
“…The AAV-based model, therefore, is most complementary to the existing transgenic mouse models, which largely lack the neurodegeneration and inflammation aspects for as yet unknown reasons. 4,5 The data further validate the AAV-based model for mechanisms that underlie tau-induced neurodegeneration downstream of the amyloid connection in AD and are relevant in primary tauopathies.…”
Section: Tau-mediated Neurodegeneration Is Closely Linked To Neurovasmentioning
confidence: 84%
See 2 more Smart Citations
“…The AAV-based model, therefore, is most complementary to the existing transgenic mouse models, which largely lack the neurodegeneration and inflammation aspects for as yet unknown reasons. 4,5 The data further validate the AAV-based model for mechanisms that underlie tau-induced neurodegeneration downstream of the amyloid connection in AD and are relevant in primary tauopathies.…”
Section: Tau-mediated Neurodegeneration Is Closely Linked To Neurovasmentioning
confidence: 84%
“…1 This model robustly recapitulates neurodegeneration in vivo, which is largely lacking in transgenic mouse models of amyloidopathy and tauopathy. 4,5,9,10 We observed that protein tau, present in an apparent oligomeric state, effected cellular demise via non-apoptotic mechanisms, and a large panel of markers implicated inflammation as a major actor. 1 The third major defect in AD-affected brain, neuroinflammation, was thereby implicated in the novel AAV-based model.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Genetic data have implied that deranged tau-microtubule interactions induced either by phosphorylation or increased levels of tau, contribute to or even are sufficient to cause synaptic and dendritic degeneration in primary tauopathies (35)(36)(37). It has been reported that transfection of tau in mature neurons leads to an improper distribution of tau into the somatodendritic compartment with concomitant degeneration of synapses, as seen by the disappearance of spines and presynaptic and postsynaptic markers (3,7).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of NFT formation is unclear. Soluble oligomers are thought to be tau's most neurotoxic conformation (Jaworski et al, 2010), so NFT formation may play a neuroprotective role by sequestering these oligomers (Spires-Jones et al, 2011).…”
Section: Introductionmentioning
confidence: 99%